IMPROVING STUDENTS’ EXPRESSIVE WRITING ABILITY USING BRAINSTORMING TECHNIQUES - Dian Fera Pratiwi; Rahmah Julianti (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
This research aims to find out whether the use of brainstorming significantly improves the expressive writing ability of the first-year students of the accommodation department of SMK Negeri 8 Makassar, South-Sulawesi, Indonesia. The research employed a pre-experimental method with a one-group pretest and posttest design. The sample was chosen by applying a cluster random sampling technique. The data were collected through writing tests. The results of the test were analyzed using the SPSS 16.00 version. The use of brainstorming as part of the treatment was chosen because it can attract the interest of the students and trigger more ideas. In line with that, the research results showed that there was an improvement in the students’ expressive writing ability between the pretest and posttest after the treatment. Based on the result, it can be concluded that the use of brainstorming significantly improves students’ expressive writing abilities. More research is needed to improve learning quality, and future researchers are hoped to address any flaws discovered in this study.